Implementasi Pemetaan Industri Pariwisata Olahraga Di Farm Valley Care Desa Kare Madiun Program Magang Kedaireka Tahun 2022 - Arsyah Ali Munawar; Purbodjati Purbodjati (LPPM Politeknik Pratama, 2023)
Mapping the sports tourism industry aims to obtain comprehensive information about the sports tourism industry, such as the types of sports that are popular and the facilities available. Farm Valley Care Tourism is a tourist destination located in Kandangan Kare Village, Madiun Regency, which was built in August 2022. Through the Kedaireka program, this tourism carries the concept of CARE (Camping, Agriculture, Recreation and Education), so that various potentials can be utilized. This research uses qualitative research and field work. The data collection techniques used were observation, interviews and documentation. The data analysis technique used is SWOT analysis to determine the strengths, weaknesses, opportunities and threats that Farm Valley Care tourism has in the tourism development process. Using research informants as data sources. The results of the SWOT analysis in implementing mapping at Farm Valley Care tourism show that in terms of quantity, the strengths are greater than the weaknesses. Opportunity factors outweigh threat factors. 1) Prominent strengths: Significant impact of mapping carried out by managers. 2) Weaknesses that influence: Socio-economic impact. 3) The most important opportunity: Cooperation with various related parties. 4) The riskiest threat: The company's finances are disrupted due to cost overruns.